2019
DOI: 10.3233/hsm-180463
|View full text |Cite
|
Sign up to set email alerts
|

IT capability, capital availability and firm performance

Abstract: Information technology capability (ITC) enhances firm performance, reflecting the constructs' positive relation. Namely ICT enables continual improvements in uncertain environments, despite its extant shortcomings. This article assesses the role that ITC plays in firm performance, mediated by capital availability and sustainable competitive position (SCP). Research hypotheses are tested through structural equation modeling, using the analysis moments of structure (AMOS) statistical software, applied on the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Technology advancement is an important incident of the different performance of the organizations [40,41]. Over the past decades, several researchers explored the impact of technology integration and revealed the positive connection on organizational performance [1,40,41]. The study of [41] concluded the positive relationships between technology and organizational performance.…”
Section: Technological Advancement (Tad) Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Technology advancement is an important incident of the different performance of the organizations [40,41]. Over the past decades, several researchers explored the impact of technology integration and revealed the positive connection on organizational performance [1,40,41]. The study of [41] concluded the positive relationships between technology and organizational performance.…”
Section: Technological Advancement (Tad) Andmentioning
confidence: 99%
“…The study of [41] concluded the positive relationships between technology and organizational performance. A study of [42] unveiled the significant relationships between technology and project performance in terms of R&D. In general, there are several studies that have recommended the positive connection between the integration of technology and organizational performance as well as encourages the organizational to advance its technological capabilities [1,14,39,41]. However, the literature is witnessed that there is still lack of known studies that examined the connection of technological advancement (TAD) on organizational project performance (OPP).…”
Section: Technological Advancement (Tad) Andmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the functional and process strategies are encompassed under the digital transformation strategy, with a close focus on policy and the competitive environment. For most firms, digital transformation is initiated at an early stage, and their strategic goals are to improve internal operation efficiency and reduce operation costs, so as to improve their competitiveness [31]. For the time being, most companies still need a long time to complete their digital transformation.…”
Section: Discussionmentioning
confidence: 99%